MENUMBUHKAN KREATIVITAS ANAK DI SEKOLAH - Haryanto, Haryanto (Jurnal Cakrawala Pendidikan, 2016)
Learning conditions in the school setting all this ti tlch as been considered insufficient in supporting children’s creativity. This unfavorable learning system is not conlplelcly the teacher’s fault, or that of those who are directly or indirectly involved in implementing children’s, education at schools. Therc are many in[eirelaled variables and it is difficult to inlcrvcnc among them so that they result in undcsirable nlodels or patterns. Efforts to foster children’s creativity can be donc by teachers at schools by developing intrincic creativily motivation in the teaching-learning process by changing convcnl onal into creative patterns, through enforccmcnt and obycctive dimensions, and thorugh reduction and actualization. Aspects necessary to foster, anlong others, are appreciating, dcdicating, Icarning-playing, and self-focusing.